CAESAREAN SECTION INCIDENTS AND COST IN WEST SUMATRA: A COMPARATIVE STUDY BETWEEN PRIVATE AND PUBLIC HOSPITALS UNDER INA CBGS SYSTEM - Aladin Aladin; Martga Bella Rahimi (Jurnal Kesehatan Masyarakat Andalas, 2021)
Since its first launched in 2014, many hospitals claimed to have financial loss due to inequality between hospital real tariff and BPJS payment. It is important to identify the characteristics and trends of caesarean deliveries in hospitals prior to measuring the efficiency level under INA-CBGs system. However, until now there is yet to be a descriptive study to understand this issue comprehensively. To fill this research gap, this study aimed to compare caesarean section incidents and costs between private and public hospitals in West Sumatra, Indonesia. This study is expected to describe real situation related to caesarean cases and explore the preference of patients in the province for caesarean deliveries. This study was retrospective and cross-sectional design of caesarean section in all West Sumatran hospitals under INA-CBGs system. The data used was taken from BPJS region West Sumatra-Riau-Jambi for period 2016 to 2018. During that period, almost 59 thousand caesarean section were performed, of which 64% in private hospitals and 36% in public hospitals. Within three years, caesarean cases in private hospitals were almost doubled while public hospitals showed a decreasing trend. In 2018, three quarter of caesarean costs was paid by BPJS to private hospitals while public hospitals only received a quarter of total costs.